Teaching and Learning Vocabulary with Duolingo: Teacher’s and Students’ Perception of Senior High School 4 Tanjungpinang - Nurfadilah, Nurfadilah; Rizwana, Nurul Atiqah; Sihite, Glorya Serepuli; Sefiani, Ayona Dwi; Pohan, Erwin (Melior : Jurnal Riset Pendidikan dan Pembelajaran Indonesia, 2024)
This study aims to explore the perspectives of teachers and students on the use of Duolingo for vocabulary learning. The research was conducted at Sekolah Menengah Atas Negeri 4 Tanjungpinang on November 8, 2024. The respondents of this study included one teacher and thirty students from Class Eleven Two Point Two, selected to represent perceptions and the effectiveness of using the Duolingo application. The method employed in this study was a descriptive quantitative approach. Data were collected through questionnaires. The findings revealed that some teachers and students were either unaware of the application or familiar with it but did not use it. One teacher stated that the main reason for not using the application was having never heard of Duolingo before. Additionally, sixty-six point seven percent of student respondents reported that they had never used the application, while thirty-three point three percent indicated they had used it. However, there is a notable interest among students in trying the application in the near future and a willingness to learn using Duolingo if implemented by teachers in the classroom. The conclusion of this study is that, although the teacher and the majority of student respondents had not used the application, they expressed openness and optimism about its potential.